2020
DOI: 10.1088/1402-4896/ab9e96
|View full text |Cite
|
Sign up to set email alerts
|

Spectral analysis and consensus problems for a class of fractal network models

Abstract: Because of the application of fractal networks and their spectral properties in various fields of science and engineering, they have become a hot topic in network science. In this paper, a class of fractal network models Gm(t) based on the fractal cactus model is studied whose structure is controlled by the positive integer coefficient m and the number of iterations t. After analyzing the structure and construction of network model Gm(t), the iterative relation of spectrum of Laplacian matrix corresponding to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Spectral analysis of graphs has become increasingly popular with researchers from various scientific fields owing to its extensive applications in physics, communication, transportation, chemistry, biology, and so on. Over the past decades, there has been particular interest in the study of the eigenvalues and eigenvectors of the normalized Laplacian matrix, since it can unveil structural properties and the influences of various topological structures on the dynamic processes of a graph [1][2][3][4][5][6]. The normalized Laplacian matrix, which is closely related to the structure and dynamic process of the graph, was initiated by Chung [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spectral analysis of graphs has become increasingly popular with researchers from various scientific fields owing to its extensive applications in physics, communication, transportation, chemistry, biology, and so on. Over the past decades, there has been particular interest in the study of the eigenvalues and eigenvectors of the normalized Laplacian matrix, since it can unveil structural properties and the influences of various topological structures on the dynamic processes of a graph [1][2][3][4][5][6]. The normalized Laplacian matrix, which is closely related to the structure and dynamic process of the graph, was initiated by Chung [7].…”
Section: Introductionmentioning
confidence: 99%
“…And a variety of network models based on the fractal network model have been extensively studied [29][30][31][32]. Furthermore, the fractal cactus model and its variations are also important fractal network models that have been studied extensively in recent years and can be used to study the topology and dynamic properties of molecular polymer networks [5,33,34].…”
Section: Introductionmentioning
confidence: 99%
“…Existing studies have demonstrated that calculations of the Laplacian eigenvalues face an enormous challenge because the eigenvalues are dominated by the network topology [9][10][11]. It is of interest to explore diverse methods to reveal the correlation between the topology and the coherence [12,13]. Particularly, for some fractal networks [14,15], such as Koch networks [16], Vicsek fractals [1], Sierpiński graphs [17], are all good candidate network models to derive an exact scaling of network coherence regarding the network size.…”
Section: Introductionmentioning
confidence: 99%